Structural and Vibrational Study on Monomer and Dimer Forms and Water Clusters of Acetazolamide - Ozel, Aysen E.; Gunduz, Serda Kecel; Celik, Sefa; Akyuz, Sevim (Journal of Spectroscopy, 2013)
Experimental IR and Raman spectra of solid acetazolamide have been analysed by computing the molecular structures and vibrational spectra of monomer and dimer forms and water clusters of acetazolamide. The possible stable conformers of free acetazolamide molecule in the ground state were obtained by scanning the potential energy surface through the dihedral angles, D1 (1S-2C-6S-9N), D2 (4N-5C-12N-14C), and D3 (5C-12N-14C-16C). The final geometry parameters for the obtained stable conformers were determined by means of geometry optimization, carried out at DFT/B3LYP/6-31G++(d,p) theory level. Afterwards the possible dimer forms of the molecule and acetazolamide-H2O clusters were formed and their energetically preferred conformations were investigated using the same method and the same level of theory. The effect of BSSE on the structure and energy of acetazolamide dimer has been investigated. The assignment of the vibrational modes was performed based on the potential energy distribution of the vibrational modes, calculated by using GAR2PED program. The experimental vibrational wavenumbers of solid acetazolamide are found to be in better agreement with the calculated wavenumbers of dimer form of acetazolamide than those of its monomeric form. NBO analysis has been performed on both monomer and dimer geometries.